MANAJEMEN DINAS PEKERJAAN UMUM DAN PENATAAN RUANG (PUPR) PROVINSI RIAU DALAM PEMBANGUNAN FLYOVER DI PEKANBARU PADA TAHUN 2018 - Mardiyas, Firdaus; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Pekanbaru City is the capital of Riau Province. With a dense population in urban areas such as what happened in the city of Pekanbaru, the need for road access is increasing, roads are the main need for public access. Dense traffic flow will cause congestion because the number of roads does not match the number of vehicles available. To get around this, the Riau Provincial Government together with the Riau Province Public Works and Spatial Planning (PUPR) Office built flyovers at points prone to congestion. There are two points that are considered to be experiencing severe congestion, especially during peak hours such as morning and evening, namely at the intersection of Pasar Pagi Arengka and the SKA Mall intersection. The Riau Provincial PUPR Office as the technical implementer of the construction flyover is responsible for the success of the development, for this reason, management is needed from the Riau Province PUPR Office so that development can be in accordance with the set targets.This study aims to determine the management of the Riau Provincial PUPR Office in carrying out construction flyover in Pekanbaru City in 2018 and to find out the factors that affect the delay construction flyover in Pekanbaru City in 2018. The research location is in Pekanbaru City, namely the Riau Province PUPR Office. This research uses a qualitative approach. This type of research is descriptive. Data were collected through informants purposively. Data collection techniques using interviews and documentation.The results of this study show that the management of the Riau Province PUPR Office in the implementation of construction flyover in the city of Pekanbaru in 2018 has not been running optimally, this can be seen from the delay in completing the flyover construction from a predetermined time. The delay in completing the flyover was caused by several factors such as program planning that did not run according to what had been determined, coordination of the government structure, namely there were still differences of opinion between the PPK and PPTK, and the flyover development management program where during the development process there were some raw materials arriving late so that it hinders the development process and cannot be completed in accordance with the predetermined time. Keywords: Management,development flyover, Riau Province PUPR Office